The Influence of Job Demand and Work Environment on Employee Performance - Kumala, Fera (Lentera Ilmu Nusantara, 2023)
This research discusses how job demands and the work environment influence employee performance. Work demands can cause stress and fatigue in employees, but a good work environment can improve employee performance. The survey method uses a quantitative method using simple random sampling. Data was collected through questionnaires and analyzed using the R-squared algorithm analysis and path coefficient bootstrapping in SmartPLS. The research results show that job demands have a significant negative influence on employee performance, while the work environment has a significant positive influence on employee performance. This study suggests the importance of managing and maintaining job demands at a moderate level and the importance of a comfortable ergonomic work environment in improving employee performance. This study highlights the importance of managing work demands and providing a conducive work environment to improve employee performance.